Disulfiram inhibits migration, invasion and epithelial-mesenchymal transition of gastric cancer cells via β-catenin/CTSB pathway - XianYi Zhou; JiuLin Li; XiuYong Liao; ChengYu Ding; SaiJiao Na; JiangRong Du; QingHui Meng; Peng Zheng; Fan Sun (Advances in Cancer Biology - Metastasis)
DSF is a well-known alcohol withdrawal agent that has shown considerable anticancer effects in preclinical studies. In the present study, we aimed to elucidate the mechanism by which DSF and CTSB modulate of the migration and invasion of GCs. Our results illustrate that DSF plays a pivotal role in suppressing tumor migration, invasion, and EMT in GC by modulating CTSB expression. Furthermore, DSF was found to aggravate the reduction in β-catenin expression via GSK-3β, consequently inhibiting CTSB expression, which has a pronounced effect on invading gastric cancer cells as a metastasis-promoting gene. Notably, β-catenin was found to increase CTSB transcriptional activity by binding to the promoter of CTSB, leading to an increase in CTSB protein levels. Collectively, our findings elucidate the molecular mechanism by which DSF suppresses EMT, migration, and invasion in GC through the GSK-3β/β-catenin/CTSB pathway, underscoring the potential of CTSB as a therapeutic target for GC.